The Mismatch of Present and Required Future Workforce Skills of Manufacturing Industry - Mohd Noor, Noor Nazihah; Rodzalan, Shazaitul Azreen; Mohamed Saat, Maisarah; Abdullah, Nor Hazana; Othman, Aniza; Harcharanjit Singh, Harcharanjit Singh; Mohd Emran, Natrah (semarak ilmu, 2024)
Manufacturing is one of the vital industries in Malaysia that contributes to the national Gross Domestic Product (GDP) and provides employment for society. The manufacturing sector involves the use of various technologies in order to produce output. However, technological advancement has affected the manufacturing sector mainly in terms of skills demanded. Furthermore, studies focusing on skills demanded in the future from the manufacturing industry perspective regarding Industry 4.0 remain scarce. Therefore, this study aims to identify the present and future skills and determine the differences in the skills demanded. This paper intends to determine mismatch encountered concerning skills demanded by the industry due to the rise of Industry 4.0. The method used in this study was the review of literature on the skills demanded in the manufacturing industry obtained from journal articles, magazines, books and online news that were closely related to the keywords and research area. This paper emphasised the impact of the skills demanded by the manufacturing industry and the skills needed in the future for manufacturing in Malaysia. Most research has discussed the skills set based on the employers and universities’ perspectives. The findings of the study found that there is a differences and mismatch between the present and future skills demanded by manufacturing industry. Therefore, the future studies required to conduct the study related to the future workforce skills in order to provide clear sight of the future workforce skills in the specific industries.